Pengaruh Rest Dan Ice Terhadap Pengurangan Nyeri Akut Pada Penderita Sprain Ankle Stadium Akut Di Rs Advent Medan - Parisco Simbolon; Trisno Susilo; Ronald Erwansyah (Jurnal Kesehatan dan Fisioterapi, 2022)
Ankle is a joint that supports the body to maintain balance when walking on uneven surfaces. These joints are composed of bones, ligaments, tendons, and connective tissue bundles. The ankle joint is formed by four bones, namely the tibia, fibula, talus and calcaneus. The main movements of the ankle joint occur in the tibia, talus and calcaneus. The purpose of this study was to determine pain in the acute stage of ankle sprain after being given rest and ice therapy for three consecutive days. This type of research is a type of quantitative research that is quasi-experimental with a one-group pre-test and post-test design approach. Prior to the intervention, respondents were given a pretest or pain scale measurement using the VAS. The results showed that the effect of rest and ice on reducing acute pain in patients with acute ankle sprains at the Medan Adventist Hospital was 0.002. Which is if Sig < 0.05 then there is a significant effect. The conclusion of this study concludes that there is a significant effect of rest and ice on the reduction of acute ankle sprain pain in the acute stage. Keywords: Acute pain, ankle sprain, rest and ice therapy